B-Site Doping in Lanthanum Cerate Nanomaterials for Water Electrocatalysis. Issue 2 (9th January 2020) - Butt, Tehmeena Maryum; Janjua, Naveed Kausar; Mujtaba, Ayesha; Zaman, Shabana Ali; Ansir, Rotaba; Rafique, Ammara; Sumreen, Poshmal; Mukhtar, Maria; Pervaiz, Maria; Yaqub, Azra; Akhter, Zareen; Yasin, Tariq; et al.
Abstract : There are only scarce reports on using lanthanum cerates in water electrocatalysis. The electrocatalytic facility in water-splitting is manifested in two of the electrochemical output parameters: the lower onset potential and the higher peak current response. The robustness of the envisioned scheme of using lanthanum cerates perovskite (LaCeO3 ; LCO) in combination with doped compositions provides better electrochemical results for water-splitting when comparing to the use of costly metallic or alloy nanomaterials. Lanthanum cerates were researched for the B-site doping effect on the resulting chemistry for the water electrocatalysis. Series of LaCe1–x Mx O3+ δ (LCMO; M = Fe 3+, Cr 3+, Cu 2+, Zn 2+ ; x = 0.02─0.10) nanopowders were synthesized and tested electrochemically by using cyclic voltammetry and impedance analysis for water-splitting in alkaline methanol at ambient conditions. The oxygen evolution reaction (OER) was evidenced by the multifold water-splitting current with perovskite powders coated on to the glassy carbon (GC) electrode. An obvious correspondence was detected between the electrocatalytic activity and the morphological, structural properties of perovskite ceramic powders.